Effects of warm-up, post-warm-up, and re-warm-up strategies on explosive efforts in team sports: A systematic review - Silva, L. M.; Neiva, H. P.; Marques, M. C.; Izquierdo, M.; Marinho, D.A. (Sports Medicine, 2018)
Background: In team sports, it is imperative that the warm-up improves acute explosive performance. However, the exact strategies, methods, and consequences of different warm-up practices remain unclear. A time delay between the warm-up and match and during half-time could negate the positive metabolic effects of the warm-up. Objectives: We conducted a systematic review to synthesize and analyze the potential effects of strategies during a warm-up (before match), post-warm-up (time between the end of warm-up and the start of a match), and re-warm-up (half-time break within a match) on explosive performance in team sports. Furthermore, we examined optimal warm-up strategies based on the included studies. Methods: We performed a search of four databases (Web of Science, Scopus, PubMed, and ScienceDirect) for original research articles published between January 1981 and August 2017. A total of 30 articles met the inclusion criteria, and the Cochrane risk of bias tool was used to assess the risk of bias. The results of the included studies were recalculated to determine effect sizes using Cohen`s d. Results: A warm-up comprising 8 sets of 60-m sprints (- 2.19%, d = 1.20) improved sprint performance. Additionally, 7 min of dynamic exercises after 5 min of jogging improved sprint (- 7.69%, d = 1.72), jumping (8.61%, d = 0.61), and agility performance (- 6.65%, d = 1.40). The use of small-sided games also seems to be a valid strategy, especially for jumping performance (6%, d = 0.8). These benefits resulted from the warm-up strategies combined with some passive rest (between 2 and 10 min) before the main performance. In this post-warm-up period, the use of heated garments could result in better outcomes than simple rest (- 0.89%, d = 0.39). However, if the transition was longer than 15 min, before entering the match, performing a re-warm-up with short-term explosive tasks to reactivate was the most effective approach (- 1.97%, d = - 0.86). At half-time, heated garments maintained better sprint (- 1.45%, d = 2.21) and jumping performance (3.13%, d = 1.62). Conclusion: Applying properly structured strategies in the warm-up and avoiding a long rest in the post-warm-up improves explosive performance. Studies tend to recommend a short active warm-up strategy (10-15 min), gradually increasing intensity (~ 50-90% of maximum heart rate), and the use of heated garments soon after the warm-up to maintain muscle temperature. However, 2 min of active re-warm-up with short-term sprints and jumps should be needed for transitions longer than 15 min (~ 90% of maximum heart rate). Last, at the half-time re-warm-up, combining heated garments to maintain muscle temperature and performing an active strategy, with explosive tasks or small-sided games for 5 min before re-entering the game, resulted in better explosive performance than 15 min of resting. Abstract from author